The dimension of Malaysian ethnic cultures in an organization / Ibrahim Zahari - Zahari, Ibrahim (2006)
The embryo of the research was an extensive study focused on the dimension of Malaysian cultures in an organization in Malaysia. The field of vision encompasses of dimension of Malaysian ethnic cultures of the Malays, Chinese and Indians from different cultural background and religious beliefs. Hofstede's (1980) cultural dimensions were used to examine the Malaysian ethnic cultures at the workplace in the organization. The basic objectives have been to examine Hofstede's (1980) model in different organizational setting. Hofstede (1980) make a study and used IBM as an organization, while the present study test Hofstede's cultural dimension in Matsushita for various reasons. First the study is interested to examine whether the initial findings by Hofstede (1980) for Malaysia at IBM held true for companies operating under different setting. Secondly the study is interested to examine whether Malaysian ethnic groups share similar work culture at the workplace in the organization. The present study examines the dimensions of Malaysian ethnic cultures of the Malays, Chinese and Indians in an organization. The cultural research undertaken in Malaysia thus far failed to distinguish between the various ethnic groups. The research undertaken by Hofstede (1980; 1991) on Malaysia was conducted as a whole and it is therefore difficult to make predictions about the direction of differences. Hofstede (1980) used dimension of power distance, uncertainty avoidance, individualism/collectivism and masculinity/femininity to measure Malaysian cultural dimensions. Hofstede's (1980) cultural dimension for Malaysia is high power distance, low uncertainty avoidance, low individualism and medium masculinity. The finding of the present study offer partial support for Hofstede's dimension where the result suggested that power distance in Malaysia is still high and masculinity is still moderate. Similarly the level of uncertainty avoidance is high and individualism is low in Malaysia over the past few decades.